Using Metamaterial structures with frequency agile basestations - Dehm-Andone, Gunther; Adamiuk, Grzegorz; Fischer, Georg (German Microwave Conference (GeMiC 2006), 2006)
http://duepublico.uni-duisburg-essen.de/servlets/DerivateServlet/Derivate-14694/Final_Papers/GM0112-F.pdf
elib2cris::1512001600,dehm-andone2006